2014
DOI: 10.1002/etc.2770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bisphenol A on mineral nutrition in soybean seedling roots

Abstract: Bisphenol A (BPA) is a ubiquitous chemical in the environment and potentially harmful to plants. However, relevant studies of the effects of BPA on plants are relatively scarce. In the present work, the effects of BPA on the biomass (fresh wt and dry wt), absorptive function (activity and absorptive area), and mineral element levels in soybean (Glycine max L.) seedling roots treated with 1.5 mg L(-1) , 3.0 mg L(-1) , 6.0 mg L(-1) , 12.0 mg L(-1) , 24.0 mg L(-1) , 48.0 mg L(-1) , and 96.0 mg L(-1) BPA were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Compared to the three growth stages, with the developing of soybean root structure and function, and the increasing of biomass, BPA stress on unit biomass of soybean roots was decreased 37 . Previous studies showed that low-dose (1.5 mg·L −1 ) BPA exposure can promote roots to absorb and make use of microelements (such as Mg and Mn) 43 , and microelements can be used to synthesize antioxidants to resist ROS oxidative stress 44 . The resistance of soybean roots to BPA stress at three growth stages followed the order: seed-filling stage > flowering and podding stage > seedling stage.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the three growth stages, with the developing of soybean root structure and function, and the increasing of biomass, BPA stress on unit biomass of soybean roots was decreased 37 . Previous studies showed that low-dose (1.5 mg·L −1 ) BPA exposure can promote roots to absorb and make use of microelements (such as Mg and Mn) 43 , and microelements can be used to synthesize antioxidants to resist ROS oxidative stress 44 . The resistance of soybean roots to BPA stress at three growth stages followed the order: seed-filling stage > flowering and podding stage > seedling stage.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulatory effects of low-concentrations BPA and the inhibitory effects of higher-concentrations BPA on the accumulation of mineral elements in soybean roots were reported in our previous studies [13]. It is well known that plant roots absorb mineral elements mainly by active and passive absorption [30].…”
Section: Discussionmentioning
confidence: 85%
“…In other words, increases in contents of minerals were related to the increased activities of respiratory enzymes, and decreased enzyme activities led to decreases in contents of minerals. In addition, our previous study showed that all concentrations of BPA caused increases in contents of Ca, Fe, and Cu in soybean roots ; furthermore, the accumulations of Ca, Fe, and Cu were negatively correlated with activities of respiratory enzymes in roots after BPA exposure and withdrawal of BPA exposure (Table ). This phenomenon may be related to the different physiological functions or the demand of soybean seedlings for the minerals under stress conditions .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations